P234 QVA149 once daily improves lung function, dyspnoea and health status independent of prior medications and disease severity: the SHINE study. (14th November 2013) - Chapman, KR; Bateman, ED; Gallagher, N; Hu, H; Banerji, D
Abstract : Introduction: QVA149 is a novel, inhaled, once-daily, fixed-dose combination of the long-acting β2 -agonist (LABA) indacaterol and the long-acting muscarinic antagonist (LAMA) glycopyrronium (NVA237) in development for the maintenance treatment of chronic obstructive pulmonary disease (COPD). The SHINE study compared the effects of QVA149 110/50 µg, indacaterol 150 µg, glycopyrronium 50 µg, tiotropium 18 µg and placebo in patients with COPD. 1 Here, we present the data on improvements in lung function (forced expiratory volume in 1 second area under the curve [FEV1 AUC5 min-4 h ] and trough FEV1 ), transition dyspnoea index (TDI) and St George's Respiratory Questionnaire (SGRQ - total score) by prior medication use and COPD disease severity subgroups. Methods: In this 26-week, multicentre, double-blind, parallel-group, placebo- and active-controlled (open-label tiotropium) study, patients aged ≥40 years with moderate-to-severe COPD (post-bronchodilator FEV1 /forced vital capacity (FVC) <0.7 and FEV1 ≥30% to <80% predicted) and a smoking history of ≥10 pack-years were randomised to receive once-daily QVA149, indacaterol, glycopyrronium, tiotropium or placebo (2:2:2:2:1). Results: Of the 2144 patients (mean age 63.9 years; mean FEV1 post-bronchodilator 55.2% predicted) who were randomised (QVA149 [ n = 475], indacaterol [ n = 477], glycopyrronium [ n = 475], tiotropium [ n = 483] and placebo [ n = 234]), 89.1% completed the study. QVA149 showed significant improvements in lung function, dyspnoea and health status compared with placebo in patient subgroups based on prior medication use and COPD disease severity (Table 1 ). Additionally, FEV1 AUC5 min-4 h was significantly improved for QVA149 versus placebo (p < 0.001) regardless of the prior medication use and disease severity. Conclusion: With once-daily QVA149, significant improvements were seen in both moderate and severe COPD patients and independent of medications used before recruitment and randomisation into the SHINE study. Reference: Bateman et al . Dual bronchodilation with QVA149 versus single bronchodilator therapy: the SHINE study. Eur Respir J. 2013 May 30. [Epub ahead of print].